On the Occurrence and Multimerization of Two-Polypeptide Phage Endolysins Encoded in Single Genes - Daniela Pinto; Raquel Gonçalo; Mariana Louro; Marta Sousa Silva; Guillem Hernandez; Tiago N. Cordeiro; Carlos Cordeiro; Carlos São-José (Microbiology Spectrum, 2022)
ABSTRACT Bacteriophages (phages) and other viruses are extremely efficient in packing their genetic information, with several described cases of overlapping genes encoded in different open reading frames (ORFs). While less frequently reported, specific cases exist in which two overlapping ORFs are in frame and share the stop codon. Here, we studied the occurrence of this genetic arrangement in endolysins, the phage enzymes that cut the bacterial cell wall peptidoglycan to release the virion progeny. After screening over 3,000 endolysin sequences of phages infecting Gram-positive bacteria, we found evidence that this coding strategy is frequent in endolysin genes. Our bioinformatics predictions were experimentally validated by demonstrating that two polypeptides are indeed produced from these genes. Additionally, we show that in some cases the two polypeptides need to interact and multimerize to generate the active endolysin. By studying in detail one selected example, we uncovered a heteromeric endolysin with a 1:5 subunit stoichiometry that has never been described before. Hence, we conclude that the occurrence of endolysin genes encoding two polypeptide isoforms by in-frame overlapping ORFs, as well as their organization as enzymatic complexes, appears more common than previously thought, therefore challenging the established view of endolysins being mostly formed by single, monomeric polypeptide chains. IMPORTANCE Bacteriophages use endolysins to cleave the host bacteria cell wall, a crucial event underlying cell lysis for virion progeny release. These bacteriolytic enzymes are generally thought to work as single, monomeric polypeptides, but a few examples have been described in which a single gene produces two endolysin isoforms. These are encoded by two in-frame overlapping ORFs, with a shorter ORF being defined by an internal translation start site. This work shows evidence that this endolysin coding strategy is frequent in phages infecting Gram-positive bacteria, and not just an eccentricity of a few phages. In one example studied in detail, we show that the two isoforms are inactive until they assemble to generate a multimeric active endolysin, with a 1:5 subunit stoichiometry never described before. This study challenges the established view of endolysins, with possible implications in their current exploration and design as alternative antibacterials.